The Influence of Servant Leadership and Organizational Culture on Employee Performance, with Work Motivation as a Mediating Variable, at the Ambon City Transportation Agency - Semuel Souhoka (West Science Business and Management, 2026)
This study aims to analyze the influence of Servant Leadership and Organizational Culture on Employee Performance, with Work Motivation as a mediating variable at the Ambon City Transportation Agency. The study population consisted of all employees (50 individuals), who were sampled using census sampling. Data were analyzed using Partial Least Squares (PLS). The results indicate that Servant Leadership and Organizational Culture have a positive and significant effect on Work Motivation and Employee Performance. Furthermore, Work Motivation was found to mediate the influence of Servant Leadership and Organizational Culture on employee performance. These findings underscore the importance of implementing servant-based leadership and a supportive organizational culture to enhance performance within government agencies.